Groups and individuals: conformity and diversity in the performance of gendered identities1. (23rd October 2018) - Evans, Robert; Collins, Harry; Weinel, Martin; Lyttleton‐Smith, Jennifer; O'Mahoney, Hannah; Leonard‐Clarke, Willow
Abstract: The nature and role of social groups is a central tension in sociology. On the one hand, the idea of a group enables sociologists to locate and describe individuals in terms of characteristics that are shared with others. On the other, emphasizing the fluidity of categories such as gender or ethnicity undermines their legitimacy as ways of classifying people and, by extension, the legitimacy of categorization as a goal of sociological research. In this paper, we use a new research method known as the Imitation Game to defend the social group as a sociological concept. We show that, despite the diversity of practices that may be consistent with self‐identified membership of a group, there are also shared normative expectations – typically narrower in nature than the diversity displayed by individual group members – that shape the ways in which category membership can be discussed with, and performed to, others. Two claims follow from this. First, the Imitation Game provides a way of simultaneously revealing both the diversity and 'groupishness' of social groups. Second, that the social group, in the quasi‐Durkheimian sense of something that transcends the individual, remains an important concept for sociology.